Pengaruh Rendaman Air Laut pada Mutu Campuran Aspal Terhadap Nilai Karakteristik Marshall - Batubara, Hamdan; Putra, Sony Adiya; Abrar, Aidil; Srihandayani, Susy (SLUMP TeS : Jurnal Teknik Sipil, 2024)
Water is still the main enemy of asphalt, especially in coastal areas adjacent to the sea. In general, seawater has a degree of corrosion. Waterlogged roads affect the strength and stability of the road surface so that the quality of the road can decrease over time. Road damage is a problem that often arises in Indonesia. In general, the Indonesian state uses bending pavement for road infrastructure needs in various regions. The purpose of this study is to determine the value of Marshallese characteristics on seawater and freshwater immersion and to determine the effect of seawater and freshwater on asphalt. It can be concluded that the quality of AC-WC (Asphalt Concrete-Wearing Course) asphalt mixture with the same level is 6%. Soaking using sea water is more damaging to the durability of the quality of the asphalt mixture compared to soaking using fresh water with a span of 3 months. This can be seen from immersion using seawater has high stability compared to using fresh water, and has a lower flow compared to using fresh water.